2014
DOI: 10.1080/00909882.2014.982686
|View full text |Cite
|
Sign up to set email alerts
|

Co-ownership of Private Information in the Miscarriage Context

Abstract: Pregnancy loss due to miscarriage is a pervasive health issue. Although talking about the miscarriage experience with friends and family members has been linked to better adjustment, revealing this loss can be difficult because discussing a miscarriage often makes people uncomfortable. Moreover, couples often manage this information jointly as they decide whether to share the miscarriage with people outside the dyad. We conducted in-depth interviews with couples to explore the nature of co-ownership in the mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
6
31
0
1
Order By: Relevance
“…They suggested that instead, this dissimilarity reflected the intricacy of co-ownership. The findings in our study, therefore, echo other CPM studies that identify co-ownership within families as collective but not necessarily uniform or tidy (Bute & Brann, 2015;Petronio, 2010;Steuber & Solomon, 2012).…”
Section: Rq1: Privacy Ownershipsupporting
confidence: 91%
See 1 more Smart Citation
“…They suggested that instead, this dissimilarity reflected the intricacy of co-ownership. The findings in our study, therefore, echo other CPM studies that identify co-ownership within families as collective but not necessarily uniform or tidy (Bute & Brann, 2015;Petronio, 2010;Steuber & Solomon, 2012).…”
Section: Rq1: Privacy Ownershipsupporting
confidence: 91%
“…Other work on privacy management also lends credence to this idea. Bute and Brann (2015) found that couples coping with miscarriage, for instance, conceptualized their loss as a shared, but distinct experience. Partners co-owned knowledge of the miscarriage, yet they also experienced unique realities (e.g., the physical toll endured by the female partner; Bute & Brann, 2015).…”
Section: Rq1: Privacy Ownershipmentioning
confidence: 97%
“…Interns in every encounter trivialized the physical experience of expectant management by referring to it as "doing nothing," "you just wait," "just go home, wait, and do nothing," "not doing anything," or "just waiting." By describing expectant management as "doing nothing," interns neglected the active embodied process a woman's body endures during a miscarriage (see Bute & Brann, 2015) while simultaneously implying that choosing to forgo medical intervention is the equivalent of choosing to do nothing at all.…”
Section: The Discursive Medicalization Of Miscarriagementioning
confidence: 99%
“…This study was limited, for example, by the number of male interns in the sample. With Communication and Pregnancy Loss 25 only four male participants, it was not possible to assess any gendered differences that may be inherent in the speech acts surrounding an experience that is embodied by women (Bute & Brann, 2015).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Communication scholars have just begun to explore challenges parents negotiate in the face of pregnancy loss in particular. For example, authors in Silverman and Baglia's (2014) ground-breaking volume reflect on their own experiences with pregnancy loss vis-à-vis issues of great import to our field, such as healthcare providers' (lack of) social support (e.g., Brann, 2015a;Bute, 2015), the intersections between scholarship on loss and mothering with personal experiences and professional identities (e.g., Brann, 2015b;Bute, 2011), and navigating privacy following miscarriage (Bute & Brann, 2015).…”
Section: Family Communication and Baby Lossmentioning
confidence: 99%